Leveraging traits for insight into the fungal ecology of burned ecosystems - Jacob R. Hopkins; Alison E. Bennett (Ecosphere)
Abstract Fungi play key roles in the fire‐fuel feedbacks that structure ~40% of the Earth's terrestrial ecosystems, yet a general understanding of fungal responses to fire is lacking. While fire and associated stressor effects on fungi vary based on fire regime components like severity, intensity, and frequency, their influence on fungi can be categorized into three primary phases based on when they influence fungi: during fire, early post‐fire, and later post‐fire. We first identify key fire‐associated phenomic traits and similarities in fungal responses to fire across time. Then, we synthesize this information by linking fire effects to specific fungal traits and response groups to produce trait profiles useful for classifying pyrophilic fungi. The goal of this review is to consolidate fire‐associated phenomic trait data into trait profiles that can be used in combination with fungal genomic data and associated methodologies. These profiles produce an invaluable framework for understanding fungal roles in fire regimes and identify previously unknown trends in fungal responses to fire and associated stressors including heat shock responses, pigmentation, and dispersal into and out of burned environments.